(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Abstract: The methodology of teaching English in higher education institutions is an integral part of the modern education system. Today, English is widely used as a global communication language, and its learning is important not only for academic success, but also for professional development. This article examines the main aspects, methods and modern approaches of teaching English in higher education.